Pengaruh Manajemen Kas, Manajemen Piutang, dan Manajemen Persediaan Terhadap Stabilitas Keuangan Perusahaan Sub-Sektor Makanan dan Minuman yang Terdafatar di Bei Periode 2021-2023 (International Forum of Researchers and Lecturers, 2025)
This study aims to determine the influence of cash management, receivables management and inventory management on the financial stability of food and beverage sub-sector companies listed on the IDX for the 2021-2023 period. The type of research is quantitative descriptive with the type of data used in this study is seconds data and data sources in the form of company financial statements published annually by each company. The sampling technique of this study was carried out through purposive sampling with predetermined criteria. The data analysis technique in this study uses classical assumption tests and also multiple linear regression methods. In the hypothesis test, a partial test (t-test), a simultaneous test (f-test) and a determination coefficient were used. The results of this study show that the influence of cash management, receivables management and inventory management on the financial stability of food and beverage sub-sector companies listed on the IDX for the 2021-2023 period partially or simultaneously has a non-significant effect. The value of the determination coefficient that is still influenced by other variables. This research was assisted by using the Statistic for Social Science (SPSS) version 26 application to determine the level of significance of each hypothesis.